Curing the Mischiefs of Faction in the American Administrative State. (January 2016) - Cook, Brian J.
The worries American citizens express about the distorting influence of minority factions, or special interests, on public governance are as old as the republic. I briefly recount the constitutional design flaws and developmental changes that have combined to make these worries more valid than ever in an age of administratively centered governance. I then review the evidence on the nature and extent of special interest influence on the administrative process from a broad swath of scholarship. After noting the limited efficacy of attempts to limit special interest influence via minor tinkering with the separation of powers, I argue for more fundamental structural change in the form of administration as a separate, constitutionally recognized element of the separation of powers. I outline basic structural features and offer hypothetical yet plausible consequences of such a design change. The latter, I contend, are amenable to confirmation or refutation through systematic analysis of evidence that is already available from past and current governing experience.